Smoking Behaviors of Junior High School Students - Kristiani Desimina Tauho; Nesti Gulo (PT.Mantaya Idea Batara, 2023)
Smoking is a problem that cannot be resolved until now. Smoking can occur in various circles, especially among teenagers still in education. Data shows that the number of teenage smokers in Indonesia and Central Java under 15 years old has increased to 35.5% in 2019. This study uses a qualitative method that reveals the meaning behind the smoking phenomenon carried out by junior high school students, data collection techniques through interviews unstructured with an open-ended question type, the type of sample used is snowball sampling using Colaizzi's Method. The results of the study found that five themes were found that influenced the occurrence of smoking behavior in adolescents, namely: adolescent knowledge regarding the harmful substances contained in cigarettes, smoking behavior in adolescents which began at the age of children, factors influencing smoking decisions, ease of obtaining cigarettes, and the reasons it is hard to quit smoking. It can be concluded that various factors and efforts that can cause smoking behavior in adolescents are needed to prevent it from an early age.